PERISTIWA DIGLOSIA DALAM MASYARAKAT JAWA KUNA: SUATU INTERPRETASI LINGUISTIS ATAS KEHADIRAN UNSUR SERAPAN BAHASA SANSKERTA DI DALAM PRASASTI BAHASA JAWA KUNA ABAD 9 - 10 MASEHI - Kayato Hardani (Berkala Arkeologi, 2007)
The phenomenon of the presence of the Sanskrit language in Old Javanese inscriptions from the 9th to 10th century AD written by citralekha-citralekha cannot be ascertained its exact origins. From the linguistic side, the mixing of foreign vocabulary with language, natives can be said to be an indicator of the occurrence of diglossia, but on the other hand there is the fact that language is something that is inherited.